2020
DOI: 10.4025/actasciagron.v42i1.42485
|View full text |Cite
|
Sign up to set email alerts
|

Multiple resistance of Conyza sumatrensis to three mechanisms of action of herbicides

Abstract: Fleabane (Conyza spp.) is an important weed in grain production systems and is currently one of the most problematic weeds in Brazil. An important factor related to weeds such as fleabane is the characteristic of herbicide-resistant biotypes developed under selection pressure, with multiple resistance previously detected for Conyza spp. Thus, the aim of this study was to demonstrate the multiple resistance of Conyza sumatrensis to the herbicides paraquat, glyphosate, and chlorimuron. From the F2 seeds of bioty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
2
19
0
1
Order By: Relevance
“…In the dose–response experiments with tribenuron-methyl, two populations were confirmed as resistant to sulfonylureas. Both R1 and R2 were highly resistant to tribenuron-methyl, and all plants survived 16 times the recommended field dose, as reported in previous studies in G. coronaria [ 17 ] or in others broadleaf species [ 34 ], these include Descurainia sophia [ 35 ], Lamium amplexicaule [ 36 ], Papaver rhoeas [ 37 ], Conyza sumatrensis [ 38 ], Diplotaxis erucoides , and Erucaria hispanica [ 39 ]. Finally, in field trials, triazolopyrimidines (pyroxsulam + florasulam) control levels were limited or even ineffective, which suggests a possible cross resistance to this ALS family, as reported in other weed species [ 36 ].…”
Section: Discussionsupporting
confidence: 67%
“…In the dose–response experiments with tribenuron-methyl, two populations were confirmed as resistant to sulfonylureas. Both R1 and R2 were highly resistant to tribenuron-methyl, and all plants survived 16 times the recommended field dose, as reported in previous studies in G. coronaria [ 17 ] or in others broadleaf species [ 34 ], these include Descurainia sophia [ 35 ], Lamium amplexicaule [ 36 ], Papaver rhoeas [ 37 ], Conyza sumatrensis [ 38 ], Diplotaxis erucoides , and Erucaria hispanica [ 39 ]. Finally, in field trials, triazolopyrimidines (pyroxsulam + florasulam) control levels were limited or even ineffective, which suggests a possible cross resistance to this ALS family, as reported in other weed species [ 36 ].…”
Section: Discussionsupporting
confidence: 67%
“…In Erigeron species, ALS inhibitors were chronologically the second mode of action that had efficiency compromised by the selection of resistant biotypes in mid-2014 [9]. Since then, several studies have reported multiple resistance in some populations, such as a biotype resistant to EPSPS inhibitors, ALS inhibitors, and photosystem I inhibitors [3]. Another case was described with the resistance to these same mechanisms plus photosystem II inhibitory and protophorphyrinogen-oxidase (PPO) inhibitors [2].…”
Section: Discussionmentioning
confidence: 99%
“…Three Erigeron species are commonly found across South America territories: Erigeron bonariensis (L.) Cronquist, Erigeron sumatrensis (L.) Cronquist, and Erigeron canadensis (L.) Cronquist [1]. To date, many studies in the literature report Sumatran fleabane (Erigeron sumatrensis) as the most frequent species infesting soybean fields in Southern Brazil [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Another serious problem, especially in Southern Brazil, is the control of Conyza spp., since biotypes with multiple resistance have already been reported (Albrecht et al, 2020). Three species of the genus Conyza have been identified in Brazil: C. bonariensis, C. canadensis, and C. sumatrensis.…”
Section: Consequences Of Gr Soybean Cultivationmentioning
confidence: 99%